2003
DOI: 10.1039/b300032j
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring nano-flow rate of water by atomic emission detection using helium radio-frequency plasma

Abstract: Recently, high-performance nano-scale flow pumping systems have been developed for micro and miniaturized analysis systems. A novel device capable of measuring and monitoring nanoliter scale flow rates has been required for the further development of the pumping system. In this study, an atomic emission detector using helium radio-frequency plasma (RFP-AED) was used for the measurement of the nanoliter scale flow rate of water by quantitatively detecting the emission from hydrogen in the water molecules. Monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…They detected copper in solution with the observation of five atomic emission lines (203). Nakagama et al reported an atomic emission detector using a helium plasma to measure the flow rate of water in the range from 4 nL‚min -1 to 1 µL‚min -1 by quantitatively detecting the emission from hydrogen in the water molecules (204). Infrared thermal velocimetry was developed by Chung and co-workers, enabling velocity measurements in transparent MEMS-based fluidic devices ranging from centimeters to meters per second (205).…”
Section: Coupling Of Separationmentioning
confidence: 99%
“…They detected copper in solution with the observation of five atomic emission lines (203). Nakagama et al reported an atomic emission detector using a helium plasma to measure the flow rate of water in the range from 4 nL‚min -1 to 1 µL‚min -1 by quantitatively detecting the emission from hydrogen in the water molecules (204). Infrared thermal velocimetry was developed by Chung and co-workers, enabling velocity measurements in transparent MEMS-based fluidic devices ranging from centimeters to meters per second (205).…”
Section: Coupling Of Separationmentioning
confidence: 99%
“…A multitude of techniques for direct flow measurements are also offered in the literature. On-chip flow measurement techniques include particle image velocitometry (PIV), 13,14 molecular tagging velocitometry, 15 laser-induced fluorescence (LIF) time of flight (TOF), 16,17 electrical admittance, 18 bubble interface monitoring, 19,20 droplet monitoring, 21 atomic emission spectroscopy of water 22 and elastic photopolymerized microsprings. 23 These methods typically add complexity to the device and can require other expensive instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Many have shown that flow metering is possible using different sensing mechanisms such as periodic flapping motion detection, 1 thermistor based temperature difference detection with varying flow rates, 2 atomic emission detection using radio RF plasma for nanoscale flow rate metering, 3 rapid scanning using a laser-induced self-mixing effect, 4 and other methods. The heat sensing mechanism works by measuring the temperature difference in a micro channel across two points.…”
Section: Introductionmentioning
confidence: 99%